Transnational Education and Employability Development - El Halabi, Hanaa (2019)
The dissertation at hand aimed at investigating the advantages and disadvantages of Transnational Education and its impact on employability development. The researcher was able to answer the research questions in the literature review. The researcher was able to answer the question about the relevance between the TNE program and the curriculum design and pedagogy. Besides, the question about how aware TNE students are of the effect of curriculum on employability was answered. The researcher also answered the question about how HEA interference helps colleges in supporting the employability within TNE curriculum. Moreover, a mixed approach was used where interviews and surveys were conducted with students, academics, and employers to get a snapshot of the relation between curriculum and employability. The research paper concluded that the students need to acquire several skills throughout their learning journey. The skills they acquire should match the job market requirements.